Differences in Financial Performance of Firms with Established Controlling Depending on the Use of AI - Vlčková, Miroslava (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper examines the relationship between the use of artificial intelligence (AI) and the economic performance of firms with an established controlling system. The aim of the study is to assess empirically whether accounting and financial indicators differ significantly between firms that use artificial intelligence and those that do not. The research sample consists of firms with established controlling, which are divided into two groups based on their use of artificial intelligence tools. The analysis draws on accounting data and selected indicators capturing cost structure, liquidity-related asset structure and short-term financial position, as well as operating performance and cash conversion efficiency. Given the nature of the data, the nonparametric Mann-Whitney U test is employed to test for differences between the two groups. The results contribute to the ongoing discussion on the role of artificial intelligence in corporate management and controlling by providing empirical evidence on whether AI use is associated with firms’ economic outcomes.